A review on underwater shockwave processing and its application in food technology. Issue 4 (21st February 2022) - Fan, Ying; Mehta, Devanshu V.; Basheer, Iqdiam M.; MacIntosh, Andrew J.
Abstract: Underwater shockwave processing (USP) is a non-thermal food processing method where a high-energy impulse is generated near a food product submerged in a liquid. The resulting shockwave transfers energy to the food, and is used to improve quality, safety, and nutritional aspects. This review presents the origin and evolution of the technology, principles of shockwave generation, mechanism of action, and applications in the food industry. The most common food application of USP is currently meat tenderization, where it is used to improve the sensory characteristics of meat as a value-added process. The use of USP as a pretreatment process has also been investigated to increase the yield and nutritional value of extracted juice and oil via softening of plant tissues. This technique also has an impact on food-borne pathogens and spoilage microorganisms in food, however, it is more effective when combined with other hurdles. Major challenges facing the industrial implementation of underwater shockwave technology include the lack of appropriate packaging materials resistant to the disruptive effects of shockwaves, the capital investment required, and a lack of regulatory information pertaining to USP. So far, most studies of underwater shockwaves on food are at the laboratory scale and validation stage. Further research endeavors and collaboration between food scientists, engineers, and regulators are necessary to scale up this technology to industrial implementation.